RECENT RESEARCH RELATED TO Li-ION BATTERY RECYCLING PROCESSES – A REVIEW - POPESCU, Ioana Alina; DORNEANU, Sorin-Aurel; TRUȚĂ, Roxana Maria; ILEA, Petru (Studia Universitatis Babeș-Bolyai Chemia, 2022)
Recycling Li-ion batteries (LIBs) is a globally discussed issue in relation with waste management and environmental protection. This review reports the recent research and industrial progresses in LIBs recycling. After a brief introduction concerning the importance of LIBs recycling, and their structure and applications, the main aspects dedicated to LIBs recycling (pre-treatment, pyrometallurgical and hydrometallurgical processes) are presented. Greater attention has been paid to the hydrometallurgical processes due to their complexity but also because they can lead to the production of valuable products without a high ecological impact (compared to pyrometallurgical ones). Given that today, worldwide, only about 5% of spent LIBs are recycled, the data presented in our review can inspire the design and implementation of competitive technologies that fit into a sustainable circular economy that preserves the primary resources and ensures the environmental protection.